Closed Loop Identification of Distillation Column - A/L P.Vellen, Nithianantham (IRC, 2016)
Approaching to the current era of modernization, growing technology is vital especially in oil and gas industry. Nowadays in industries, loads of storages in the form of columns are kept but the most regular and common column used is distillation column. It is widely used everywhere. To be precise, determination of the output is called the feedback signal and the type of system uses is known as closed loop system. Closed loop system identification is a process of enhancing or developing the mathematical representation of a physical system with a feedback control whereas open loop system identification is the mathematical representation without a feedback control.